The Influence of Early Life Experience on Visceral Pain - Fuentes, Isabella M.; Christianson, Julie A. (Frontiers in Systems Neuroscience, 2018)
Pain is the most reported and troublesome symptom of nearly all functional disorders affecting the genitourinary and gastrointestinal organs. Patients with irritable bowel syndrome, interstitial cystitis/painful bladder syndrome, vulvodynia, and/or chronic prostatitis/chronic pelvic pain syndrome (collectively termed chronic pelvic pain syndromes) report pain severe enough to impact quality of life and often suffer from symptoms of or are diagnosed with more than one of these syndromes. This increased comorbidity between chronic pelvic pain syndromes, and with pain disorders of disparate body regions, as well as with mood disorders, can be influenced by disruptions in the hypothalamic-pituitary-adrenal (HPA) axis, which regulates the response to stress and influences the perception of pain. Experiencing trauma, neglect, or abuse in early life can permanently affect the functioning of the HPA axis. As such, a significant proportion of patients suffering from comorbid chronic pelvic pain syndromes report a history of early life stress or trauma. Here we will report on how these early life experiences influence chronic pelvic pain in patients. We will also discuss various rodent models that have been developed to study this phenomenon to understand the mechanisms underlying HPA axis dysfunction, as well as potential underlying mechanisms connecting these syndromes to one another.